Towards an integrated AlGaAs waveguide platform for phase and polarisation shaping. (20th April 2018) - Maltese, G; Halioua, Y; Lemaître, A; Gomez-Carbonell, C; Karimi, E; Banzer, P; Ducci, S
Abstract: We propose, design and fabricate an on-chip AlGaAs waveguide capable of generating a controlled phase delay of π /2 between the guided transverse electric and magnetic modes. These modes possess significantly strong longitudinal field components as a direct consequence of their strong lateral confinement in the waveguide. We demonstrate that the effect of the device on a linearly polarised input beam is the generation of a field, which is circularly polarised in its transverse components and carries a phase vortex in its longitudinal component. We believe that the discussed integrated platform enables the generation of light beams with tailored phase and polarisation distributions.